2022
DOI: 10.3390/ijms232314544
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Dim Light at Night during Pregnancy Can Affect Hormonal and Metabolic Rhythms in Rat Offspring

Abstract: Artificial light at night (ALAN) is considered an environmental risk factor that can interfere with the circadian control of the endocrine system and metabolism. We studied the impact of ALAN during pregnancy on the hormonal and biochemical parameters in rat pups at postnatal (P) days P3, P10, and P20. Control dams (CTRL) were kept in a standard light-dark regime, and ALAN dams were exposed to dim ALAN (<2 lx) during the whole pregnancy. A plasma melatonin rhythm was found in all CTRL groups, whereas in ALA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…First, the response to ALAN may depend on the onset of ALAN exposure (embryonic versus larval stage). Second, evidence shows that the parental exposure to ALAN imposes transgenerational effects on human foetuses (reviewed in [55]) and rat offspring [56]. Future research on how parental influence changes ALAN impacts on non-human animals could disentangle the role of genotypic variation, parental phenotype and its environment and give insight into potential selective pressure from ALAN.…”
Section: Discussionmentioning
confidence: 99%
“…First, the response to ALAN may depend on the onset of ALAN exposure (embryonic versus larval stage). Second, evidence shows that the parental exposure to ALAN imposes transgenerational effects on human foetuses (reviewed in [55]) and rat offspring [56]. Future research on how parental influence changes ALAN impacts on non-human animals could disentangle the role of genotypic variation, parental phenotype and its environment and give insight into potential selective pressure from ALAN.…”
Section: Discussionmentioning
confidence: 99%
“…Dim light conditions at night (~2–5 lux) alter the daily rhythm of blood glucose concentrations, phase advance Glut2 expression in hepatocytes, and suppress rhythmicity of SCN clock genes in rats, 73,74 but do not seem to affect glucose tolerance 75 . In rats, mistimed artificial light during pregnancy altered glucose tolerance, reduced absolute melatonin levels, and induced a loss of the daily rhythm of corticosterone in both the mothers and the offspring 76,77 …”
Section: Circadian Desynchrony Disturbs Glucose Metabolismmentioning
confidence: 99%
“…ALAN exposure during pregnancy or the lactating period can impact the development of MEL rhythms during early ontogeny, imposing potential long-lasting effects on the sensitivity of the circadian system in adulthood. A recent study showed that the development of the plasma MEL rhythm was delayed in offspring born to female rats exposed to ALAN during pregnancy [ 76 ]. The possible importance of MEL during pregnancy is illustrated by the fact that its levels in pregnant women substantially increase from gestational week 32 and are normalised only after delivery [ 77 ].…”
Section: Melatoninmentioning
confidence: 99%